Considerations on pollution at European level - Anane, Iuliana (Technium Social Sciences Journal, 2023)
Human activity has caused profound changes to the environment, and not infrequently the resulting effects have proven to be irreversible. Man becomes the main responsible and the most dangerous actor on the scene of pollution to the environment. Today, nature is exploited and polluted more than at any time in history. Any source of pollution becomes a disturbing factor for the smooth running of phenomena encountered at the level of natural ecosystems. Even if each ecosystem has the capacity for self-regulation, this function may be outdated in the face of dosage and the force of polluting elements. Contemporary European society feels most strongly the need for anti-pollution policies, but especially for the immediate implementation of measures to stop various phenomena and actions harmful to the environment and human life. Although the problem is real and topical, various economic and social interests reduce the number of participants with an active role in greening. This raises the need to raise broad awareness of environmental issues and encourage civil initiatives, a task that is shared between various environmental non-governmental organisations and the European Union. It currently has a broad set of rules on environmental issues, including: air quality, chemical safety, climate action, nature protection, waste management and water quality. When it comes to climate, nature and chemicals, the EU has been a pioneer in environmental and health protection, inspiring others around the world to follow suit. However, the European Union’s achievements are not just a thing of the past, but its attitude towards environmental protection is future-oriented. The preservation, protection and improvement of the quality of the environment, the protection of human health and the prudent and balanced utilisation of natural resources are objectives of the European Union’s environmental policy. This policy is based on the precautionary principle, as well as on the principles that preventive action should be taken, that environmental damage should, as a priority, be rectified at source and, last but not least, that the polluter pays.